2007
DOI: 10.1203/pdr.0b013e3181425858
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Norepinephrine and Fluid on Cerebral Oxygenation in Experimental Hemorrhagic Shock

Abstract: Few data exist regarding resuscitation of hypovolemic shock in infants, and alternative strategies such as vasopressor therapy merit further evaluation. However, the effects of norepinephrine on cerebral perfusion and oxygenation during hemorrhagic shock in the pediatric population are still unclear. Eight anesthetized piglets were subjected to hypotension by blood withdrawal of 25 mL/kg. Norepinephrine was titrated to achieve baseline mean arterial blood pressure (MAP), and cerebral oxygenation was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
3
6
0
1
Order By: Relevance
“…Meybohm et al reported on the effects of rapidly restoring cerebral perfusion pressure in piglets undergoing hemorrhagic shock and showed that brain tissue oxygenation and the tissue oxygen index could not be improved without blood transfusion. 26 Using our animal model, our findings are in agreement and demonstrate that WB is the best fluid for raising rScO 2 when used with 100% oxygen supplementation. Therefore, blood transfusion to increase total hemoglobin level to restore oxygen carrying capacity is important to brain tissue oxygenation.…”
Section: Discussionsupporting
confidence: 83%
“…Meybohm et al reported on the effects of rapidly restoring cerebral perfusion pressure in piglets undergoing hemorrhagic shock and showed that brain tissue oxygenation and the tissue oxygen index could not be improved without blood transfusion. 26 Using our animal model, our findings are in agreement and demonstrate that WB is the best fluid for raising rScO 2 when used with 100% oxygen supplementation. Therefore, blood transfusion to increase total hemoglobin level to restore oxygen carrying capacity is important to brain tissue oxygenation.…”
Section: Discussionsupporting
confidence: 83%
“…In our study the three treatments normalized PgCO 2 suggesting a normalization of splanchnic perfusion. Near infrared spectroscopy indirectly evaluates brain tissue oxygenation [ 38 ]. In our study, brain tissue oxygenation index (bTOI) diminished significantly with hemorrhagic shock and was normalized with the three treatments, but AHS produced a significantly higher increase than the other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we chose norepinephrine as a vasopressor rather than vasopressin because hemorrhagic shock causes myocardial depression and norepinephrine has been shown to increase cardiac index and myocardial performance (21)(22)(23). Moreover, norepinephrine increases cerebral perfusion pressure immediately after hemorrhagic shock (20,24).…”
Section: Discussionmentioning
confidence: 99%